Small faces - Keane, John E. 1952- (Pathé Distribution Limited, 2003)
"Glaswegian teenager Lex is torn between the artistic life of middle brother Alan and the thuggish world of elder brother Bobby." [imdb.com]
Special features: Originall theatrical trailer ; scene access ; interactive menus
Original: Großbritannien 1995
Bildformat 1.33:1 (4:3)
Keywords: Film; DVD-Video